Mortality from asthma in the state of S. Paulo, Brazil (1970-1992) - Paulo Andrade Lotufo; Isabela Judith Martins Benseñor; Cecília Amaro de Lolio (Universidade de São Paulo, 1995)
Mortality from asthma has shown important variations over time in several countries. In Brazil, a mortality study performed in the 60s, covering the cities of S.Paulo and Ribeirão Preto, and other ten cities showed that S.Paulo presented the lowest death rate from asthma among of them all. It was decided to study the time trends of deaths from asthma and from the whole set of respiratory diseases from 1970 to 1992, in the population aged 15-34 yrs. old in the State of S.Paulo, as well as to compare them with those of other countries. Asthma mortality rates during the 23 years of observation since 1975, showed an oscillatory declining pattern with a peak of deaths in the initial years. The linearization of the curve allows the calculation of Pearson's correlation coefficient that was significantly negative, suggesting a decline in the mortality over this period, mainly in the 5-9 yrs. old and 30-34 yrs. old strata. The segmentation of data between the period of ICD-9, 1970 to 1978, and of ICD-9, 1979 and subsequent years, shows that there is stability within each period, in all age-groups, except for that of 5-9 yr. olds between 1970-1978. Comparing the rates of the population aged 15-34 yrs. old for the State of S. Paulo, Brazil, with trends observed in 14 other countries, an intermediate pattern for the first triennial period (1970-1972) as well as for the subsequent triennial periods, emerges. A prevalence study of asthma, a follow up program meant for using emergency rooms and a surveillance of deaths due to all respiratory diseases and specifically to asthma are strongly recommended. A mortalidade por asma tem apresentado importantes variações em muitos países. No Brasil, um estudo de mortalidade realizado nos anos sessenta, em duas cidades do Estado de São Paulo (São Paulo e Ribeirão Preto) juntamente com outras dez cidades de outros países, mostrou que São Paulo apresentava menor coeficiente de mortalidade por asma. Foi feito novo estudo da mortalidade por asma na população do Estado de São Paulo com idade entre 5-34 anos. Foram analisadas as bases de dados do sistema oficial de mortalidade do Estado de São Paulo. Para seleção dos dados de mortalidade foram escolhidos os códigos 490 a 493 da Classificação Internacional de Doenças de 1970-1978 (CID-8) e 1979-1992 (CID-9). Os coeficientes por asma apresentaram padrão oscilatório declinante durante os 23 três anos de observação, com um pico de óbitos nos anos iniciais. O cálculo dos coeficientes de correlação, que foram negativos, sugere declínio da mortalidade no período, principalmente na faixa etária dos 5-9 anos e na dos 30-34 anos. A segmentação dos dados entre os períodos de 1970-78 (CID-8) e 1979-92 (CID-9) mostrou estabilidade em cada período, em todas as faixas etárias, exceto a 5-9 anos no período de 1970-78. Comparando os coeficientes ajustados entre os 5 e 34 anos no Estado de São Paulo e as respectivas tendências com catorze países, obteve-se padrão intermediário.